Prospective Study of Epidural Steroids for Low Back Pain in Orthopedic Department of a Tertiary Care Hospital in Surat City - Mehta, Rajendra; Rathod, Janak; Narang, Devendra; Rupani, Mihir (National Journal of Community Medicine, 2012)
Introduction: Low back pain is one of the leading problems of patients coming to Orthopedic outdoor patient department(OPD) at SMIMER. There are many modalities of treatment available for low back pain.Epidural steroid injections are one ofthe modes of treatment for low back pain. Methodology: In this study, patients were admitted for chronic low back pain and given epidural steroids for the same. They were then followed up for a period of 6 months and then results were analyzed using visual analogue scale and compared with those patients of control group who were treated conservatively using bed rest, analgesics and physiotherapy. Data was entered in Microsoft Excel and data analysis was carried out using SPSS software version 16(licensed to VNSGU). Kruskal Wallis test was applied for determining the difference in Visual Analogue Scale score among the three groups. Results: Mean age of patients was 51.52 years and standard deviation was 14.97 years. By using Kruskal Wallis test it was found that epidural steroid injections are effective significantly in reducing visual analogue score for both low back pain with radiculopathy and mechanical back pain as compared to the control group. Conclusion: Epidural steroids are an effective way of treating low back pain with radiculopathy and mechanical back pain providing significant relief to the patient.